2019
DOI: 10.5152/iao.2019.5983
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Hearing Prognosis of Ossiculoplasty in Pars Flaccida Cholesteatoma Using the EAONO/JOS Staging System

Abstract: The Journal of International Advanced Otology (J Int Adv Otol) is an international, peer reviewed, open access publication that is fully sponsored and owned by the European Academy of Otology and Neurotology and the Politzer Society. The journal is published triannually in April, August, and December and its publication language is English. The scope of the Journal is limited with otology, neurotology, audiology (excluding linguistics) and skull base medicine. The Journal of International Advanced Otology aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
11
0
2
Order By: Relevance
“…Recently, prognostic factors for short-term hearing outcomes of ossicular chain reconstruction for “pars flaccida cholesteatoma” as classified by the EAONO/JOS staging system have been reported [ 14 ]. The rate of successful hearing improvement significantly decreased with increase in EAONO/JOS stage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, prognostic factors for short-term hearing outcomes of ossicular chain reconstruction for “pars flaccida cholesteatoma” as classified by the EAONO/JOS staging system have been reported [ 14 ]. The rate of successful hearing improvement significantly decreased with increase in EAONO/JOS stage.…”
Section: Discussionmentioning
confidence: 99%
“…Even though two recent studies investigated the association of the cholesteatoma extent and hearing outcomes [ 16 , 17 ], only few studies evaluated the impact of cholesteatoma surgery on health-related quality of life (HRQoL) [ 1 , 18 20 ]. To our knowledge, no studies exist investigating the association between cholesteatoma stages as defined by a classification system and HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Although they described the number of patients treated with CWU and CWD procedures, the authors did not analyze the role of surgical technique in the recidivism rate. Fukuda et al [15] reported the short-term hearing results in a small group of patients affected by pars flaccida cholesteatoma and submitted to mastoidectomy and tympanoplasty with cartilage double-block reconstruction on the stapes. The authors classified all the cases with the EAONO/JOS staging system and used a post-operative ABG < 20 dB as success criterion, thereby finding that poorer hearing results were associated with higher EAONO/JOS stages and stapes involvement.…”
Section: Discussionmentioning
confidence: 99%